2015
DOI: 10.1371/journal.pone.0130295
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Viable Plant-Vertebrate Chimeras

Abstract: The extreme dependence on external oxygen supply observed in animals causes major clinical problems and several diseases are related to low oxygen tension in tissues. The vast majority of the animals do not produce oxygen but a few exceptions have shown that photosynthetic capacity is physiologically compatible with animal life. Such symbiotic photosynthetic relationships are restricted to a few aquatic invertebrates. In this work we aimed to explore if we could create a chimerical organism by incorporating ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…The fact that O. amblystomatis can stably survive inside the salamander suggests that these unicellular microalgae manage to evade destruction by the vertebrate host’s immune system. Attempts to reproduce this photosymbiont-vertebrate interaction under controlled experimental conditions have been undertaken by two independent research groups, who injected photosynthetic Synechococcus elongatus PCC 7942 cyanobacteria ( Agapakis et al, 2011 ) and Chlamydomonas reinhardtii ( C. reinhardtii ) microalgae ( Alvarez et al, 2015 ), respectively, into zebrafish embryos. In the first study, the authors showed higher biocompatibility of the cyanobacteria (relative to E. coli cells) with the zebrafish embryo.…”
Section: Photosymbiosis In Naturementioning
confidence: 99%
See 1 more Smart Citation
“…The fact that O. amblystomatis can stably survive inside the salamander suggests that these unicellular microalgae manage to evade destruction by the vertebrate host’s immune system. Attempts to reproduce this photosymbiont-vertebrate interaction under controlled experimental conditions have been undertaken by two independent research groups, who injected photosynthetic Synechococcus elongatus PCC 7942 cyanobacteria ( Agapakis et al, 2011 ) and Chlamydomonas reinhardtii ( C. reinhardtii ) microalgae ( Alvarez et al, 2015 ), respectively, into zebrafish embryos. In the first study, the authors showed higher biocompatibility of the cyanobacteria (relative to E. coli cells) with the zebrafish embryo.…”
Section: Photosymbiosis In Naturementioning
confidence: 99%
“…They also showed that the photosynthetic organisms were capable of surviving and proliferating inside mammalian cells when cultured under illumination. In the second study, Alvarez et al (2015) established viable plant-vertebrate chimeras, and demonstrated that both the injected algae and the zebrafish embryo/larvae could survive for several days after injection, during which time no significant innate immune response against the “photosymbiont” nor any developmental impairment of the host was observed. The results presented in both studies suggest that, up to a certain level, photosynthetic organisms are well tolerated as foreign bodies by the developing zebrafish.…”
Section: Photosymbiosis In Naturementioning
confidence: 99%
“…Interestingly, the algae remain alive and even reproduce while embryonic development takes place. This opens the possibility of future plant -vertebrate chimaeras where an additional engineering level would allow the production of useful metabolites other than oxygen [153,156].…”
Section: Synthetic Symbiosismentioning
confidence: 99%
“…On the other hand, C. reinhardtii metabolizes nitrite (NO 2 ) and releases ammonia (NH 3 ) as a nitrogen source for S. cerevisiae [151]. In (c), we display a microscope image of a chimaera zebra fish embryo containing living photosynthetic cells [152,153].…”
Section: Synthetic Cognitive Agents and Swarmsmentioning
confidence: 99%
“…The second approach is microinjection of algae or photosynthetic bacteria into animal cells (Agapakis et al 2011). Recently, the green alga Chlamydomonas reinhardtii was microinjected into zebrafish eggs and survived in embryos and larvae for a few days (Alvarez et al 2015). The main problem in maintaining microinjected algae is preventing exclusion of the algae based on allorecognition including autophagy and the ubiquitin-proteasome system.…”
mentioning
confidence: 99%